Alleged Medical Errors Reporting of Autopsied Cases as a Quality Improvement Tool - Sah, Bikash; Jha, Shivendra; Yadav, Ajay Kumar; Yadav, Bishwanath; Aryal, Bijaya Devi (Journal of BP Koirala Institute of Health Sciences, 2020)
Information obtained from autopsy is a source of continued learning for which the cases which were brought for autopsy at tertiary care center of eastern Nepal from 1st January 2016 to31st December 2017 with an allegation of death due to the medical negligence are being reported. Case 1 was filed on a doctor with an allegation of death because of not realizing about ectopic pregnancy in case of post abortion care but the doctor was saved when histopathological examination could not establish product of conception. Case 2 is with an allegation that the patient could have been saved if specific poison determination would have been done. In this case, legal duty of a doctor to take dying declaration had also not been done. In case 3, patient's request for surgical delivery was not heard and she died during normal delivery. Case 4 died following his gastro-intestinal endoscopic examination. Conclusion: This research has shown the importance of autopsy in quality improvement of medical practice.